2020
DOI: 10.3390/ani10091587
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Performance Measurement in Water Fleas by Utilizing High-Speed Videography and ImageJ Software and Its Application for Pesticide Toxicity Assessment

Abstract: Water fleas are a good model for ecotoxicity studies, and were proposed for this purpose by the United States Environmental Protection Agency, due to their easy culture, body transparency, and high sensitivity to chemical pollution. Cardiovascular function parameters are usually used as an indicator of toxicity evaluation. However, due to the nature of the heart and blood flow, and the speed of the heartbeat, it is difficult to perform precise heartbeat and blood flow measurements with a low level of bias. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…IMI exposure is known to cause a depressed heart rate. Previous experiments demonstrated that IMI exposure to D. magna could affect heartbeat by reducing the heart rate of D. magna in all of the tested concentrations [67]. In another D. magna study, a similar result was noted when D. magna was exposed to neonicotinoid insecticides.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…IMI exposure is known to cause a depressed heart rate. Previous experiments demonstrated that IMI exposure to D. magna could affect heartbeat by reducing the heart rate of D. magna in all of the tested concentrations [67]. In another D. magna study, a similar result was noted when D. magna was exposed to neonicotinoid insecticides.…”
Section: Discussionsupporting
confidence: 55%
“…A previous study has also proven that temperature can also affect the heartbeat. In Daphnia , heart rates display a good positive relationship with ambient water temperature [ 67 ]. In M. edulis , a high temperature was observed to increase the heartbeat.…”
Section: Discussionmentioning
confidence: 99%
“…The success of detecting cardiac rhythm in zebrafish by the OpenCV method promotes us to test whether our approach is also functional when applied to ultrafast heartbeat events in water fleas. We analyzed heartbeat data for Daphnia magna reported by Santoso et al [72]. The control peaks for Daphnia magna heartbeat analyzed by OpenCV method can be found in Figure S1, with a good signal-to-noise ratio.…”
Section: Use Of Opencv Methods To Detect An Ultrafast Heartbeat In Daphnia Magnamentioning
confidence: 99%
“…In previous studies, our team has developed several simple and cost-effective ImageJbased methods to conduct cardiac rhythm detection in zebrafish and Daphnia [21,26,72]. In order to effectively reduce the relative complexity for manual or semi-automated operation, in this study, we aimed to develop an automated tool for cardiac rhythm detection in zebrafish by using OpenCV.…”
Section: Overview Of Heart Rate and Rhythm Analysis Pipeline By Opencvmentioning
confidence: 99%
“…Within these factors, the environmental factor, especially temperature, is capable of inducing fast bradycardia or tachycardia [50]. Due to being ectothermic organism, changes in water temperature can significantly alter D. magna heart rate [51]. An increase in temperature will increase metabolic activity resulting in high cellular oxygen demand, which increases heart activity to fulfill the demand, while the opposite happens during low temperatures [52].…”
Section: Measurement Of Multiple Cardiac Performance Endpoints By Using Kymographmentioning
confidence: 99%